Masters of Our Own Destiny: The Nationalist Evolution of Newfoundland Premier Danny Williams - Marland, Alex (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2010)
Within Canada, the strength of Newfoundland and Labrador’s nationalism is perhaps second only to Quebec’s, and its regionalism is most comparable to Alberta’s. Since Newfoundland joined Canada in 1949, its premiers have alternated styles of exerting political pressure on the federal government and its representatives. Most recently, Premier Danny Williams has used unconventional means to obtain new revenue streams whilst, as with his charismatic predecessors, exerting an executive dominance over provincial politics. As frustrations with outsiders and dissenters have mounted, his party has further embraced nationalist rhetoric and identity politics. This essay records the related actions of the Williams administration into its second term and provides a foundation for explaining nationalism, populism, and regionalism in Newfoundland.